Perlindungan Hukum Pemegang Hak Prioritas atas Hak Guna Bangunan Di Atas Tanah Hak Pengelolaan Terkait ditolaknya Perpanjangan HGB - Kahfian NM, Resy; M, Felicitas Sri; Fitrian, Achmad (Peneliti.net, 2025)
This research examines the mechanism for using priority rights in the process of extending Building Use Rights (HGB) on Management Rights Land (HPL) according to applicable laws and regulations as well as the legal protection mechanism for HGB holders if there is a rejection of the extension of HGB located on Management Rights Land (HPL). In this research, the research addresses two problems, namely: What is the mechanism for using priority rights in the process of extending Building Use Rights (HGB) on Land Management Rights (HPL)? And what is the legal protection for Building Use Rights (HGB) holders if there is a refusal to extend the HGB located on land with Land Management Rights (HPL) status? And uses two theories, namely the land registration theory from Boedi Harsono and legal protection from Satjipto Rahardjo. The method used in this research is normative juridical research specifically a library law research or secondary adata with primary, secondary and tertiary legal sources. As for the research approach used the legislative approach, the conceptual approach and the case approach and the method of collecting the legal materials are carried out by identifying and taking an inventory of positive law, journals and other legalsources. The method used in analyzing materials grammatical interpretation and systematic interpretation are carried out as well as analogical legal construction and Argumnentum A Contrario. For the research results can be obtained the importance of Priority Rights in the context of extending Building Use Rights (HGB) on Land Management Rights (HPL). Priority Rights provide former HGB holders with the opportunity to apply for an extension after their rights expire, with certain conditions stipulated in PP No. 18 of 2021 and ATR/BPN Ministerial Regulation No. 18 of 2021. The extension process includes submitting an application, fulfilling seven requirements, assessment and decision by the authorities, and issuing an extension if approved. Apart from that, HGB holders have two legal protection mechanisms, namely preventive through an agreement stating priority rights, and repressive by filing a lawsuit in court if the application is rejected.